Analysis Externality Flyover as Public Goods on Economic and Social Conditions (Study Case: Flyover of Jl. Sultan Agung) - Nalsal Winata Sinaga, Dion; Marselina, Marselina (International Journal of Social Science, Education, Communication and Economics, 2024)
Bandar Lampung City, the capital of Lampung Province, is the hub of a variety of activities, including social, cultural, economic, and tourism related ones. The high population of Bandar Lampung City, coupled with immigrants who visit or stay, creates new problems, namely traffic jams due to population density. Flyover is being offered through the Bandar Lampung City Government in an attempt to lessen traffic congestion. Flyover Jl. Sultan Agung is one of the 11 flyovers in Bandar Lampung City that have been documented to date. This research aims to look at positive and negative externalities from economic and social aspects. The research method used is qualitative based on distributing questionnaires through closed questions with assessments on a Likert scale. There were 45 respondents in this research, with the scope being trader surrounding area flyover Jl. Sultan Agung. From the research that the existence of flyover Jl. Sultan Agung has positive and negative externalities on economics and socials aspects, referring to income and turnover, business opportunities, employment, number of customers, distribution of goods, business sustainability, competitiveness, rental costs, level of congestion, security and comfort, the culture of mutual cooperation, interaction relations, and the level of traffic accidents.